EFFECT OF EICHHORNIA CRASSIPES ZUCC. LIQUID GREEN MANURE AND POTASSIUM ON GROWTH AND PRODUCTION OF SOLANUM MELONGENA L. IN INCEPTISOL SOIL - Erwin Junaidi Lubis (Jurnal Media Akademik (JMA), 2026)
Green Eggplant (Solanum melongena L.) is a plant that is in great demand by all people. This green eggplant belongs to the solanaceae family and contains nutrients such as Vitamins A, B, C, Potassium, Phosphor, Iron, Protein, Fatty Acids and Carbohydrates. One of the ways to get good production results in Inceptisol and Inceptisol soil is to use forage fertilizer that has been composited into liquid due to complete nutrients such as N2 (2.2%), K2O (2.2%), P2O5 (3.65%), C (6.45%) and other nutrients, as well as the use of potassium nutrient fertilizer (60%) to be sufficient for the development and production of green eggplant plants. The indication of the research is because the Inceptisol soil has sufficient nutrients applied liquid green manure as much as 600 ml.polybag-1, and the soil has sufficient potassium nutrients as much as 15 g.polybag-1 and plants produce better green eggplant fruit than more or less potassium nutrients applied.